Collaboration of 4 Religious Leaders as A Driver of Moderation and Tolerance in The Concept of Rahmatan Lil Alamin Pesantren Values - Waziroh, Iro; Fuadi, Imam; Kholis, Nur (Proceedings of Annual Conference for Muslim Scholars, 2024)
The collaboration of four religious leaders (Islam, Christianity, Hinduism, and Buddhism) is important in encouraging moderation and tolerance among religious communities in Indonesia through the concept of Pesanten Rahmatan lil Alamin values. The object of this research is religious leaders who act as spiritual leaders and social activists in a multicultural society. This research uses the Systematic Literature Review (SLR) method. The research data is sourced from various journal articles, books, and related research reports. The results show that collaboration between religious leaders effectively strengthens the values of religious moderation, where religious leaders actively promote interfaith dialog, reduce social conflicts, and facilitate joint activities that reflect harmony. This collaboration also has a positive impact on the image of the Islamic-majority country of Indonesia by emphasizing the values of Rahmatan lil Alamin pesantren as a driver of religious moderation that has an impact on social stability and increased interfaith understanding in society by continuing to develop collaborative activities and dialogue, and pesantren have the potential to become a model center for religious harmony in Indonesia.